Pengembangan Bahan Ajar Muatan Pelajaran PPKn Berbasis Higher Order Thinking Skills untuk Meningkatkan Hasil Belajar Siswa Kelas VI SD Negeri 49 Bengkulu Tengah - Wiharti; Puspa Djuwita; Abdul Muktadir (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
This research is development research. The purpose of this study was to develop teaching materials to determine the feasibility and effectiveness of the developed High Order Thinking Skill (HOTS) based teaching materials. This research is a research and development which refers to 4-D proposed by Thiagarajan, namely definition, design, development, and deployment. The research subjects were class VI students at SD Negeri 49 Bengkulu Tengah. The data were obtained through observation, interviews, and test results. The results showed that the quality of teaching materials developed for material feasibility was 91.5%, language 89%, and graphics 91.25%, so it was included in the very good category. Based on the paired t-test obtained a significance value of 0.00, <0.05 then Ha is accepted, then the test decision between the posttest and pretest has a significant difference in effectiveness. The average cognitive learning achievement before using teaching materials was 44.20 and after using teaching materials was 79.75. The average value of the effectiveness of the N-gain score is 64%, which means that HOTS-based teaching materials are quite effective to use. The results of the teacher's comments at the dissemination stage were that the teaching materials were suitable for use in the learning process. The learning outcomes for the spiritual, affective, and psychomotor aspects were stated to be good.